PENGARUH LITERASI KEUANGAN DAN PENGENDALIAN DIRI TERHADAP PERILAKU KONSUMTIF SISWA SMA MUHAMMADIYAH 1 KARANGANYAR - Fuad Abdul Fattah; Mintasih Indriayu; Sunarto Sunarto (Department of Economics Education, Universitas Sebelas Maret, 2018)
This study aims to determine the presence or absence of (1) the influence of financial literacy on consumer behavior konsumtif SMA Muhammadiyah 1 Karanganyar; (2) the influence of self-control on consumptive behavior of Muhammadiyah SMA 1 Karanganyar students; This research is a type of descriptive quantitative research with correlational method. The population in this study is all students of SMA Muhammadiyah 1 Karanganyar as many as 1180 students consisting of classes X and XI. The sample in this study amounted to 93 students taken with proportional sampling technique stratified random sampling. Methods of collecting data in the form of questionnaires and documentation. Data analysis used is structural equational modeling (SEM) analysis technique. The results of this study show (1) Financial literacy has a coefficient beta -0.486 and has a t-value of 1.726> 1.66. These results indicate that literacy has a negative and significant relationship direction. (2) Self-control has a beta coefficient of 1.087 and has a t-value of 3.478> 1.66. These results indicate that self-control has a positive and significant relationship direction.